Machine Learning-based Classification Of Termite Genera - Sundresan A/L Perumal; Homathevi Rahman; Valliappan Raman; Subramanian Raja Nagendran; Bala Saatvik Thanigai Arasu; Deepakkumar Senthil Kumar; Roghan Raja (IEEE Explorer, 2024)
Indexed by Scopus